Prenatal Mancozeb Exposure, Excess Manganese, and Neurodevelopment at 1 Year of Age in the Infants’ Environmental Health (ISA) Study - Mora, Ana María (Environ Health Perspect, 2018)
BACKGROUND: Although growing evidence suggests that early-life excess manganese (Mn) impairs neurodevelopment, data on the neurodevelopmental effects of mancozeb, a fungicide containing Mn, and its main metabolite ethylenethiourea (ETU) are limited. OBJECTIVE: We examined whether prenatal mancozeb exposure and excess Mn were associated with neurodevelopment in 355 1-y-old infants living near banana plantations with frequent aerial mancozeb spraying in Costa Rica. METHODS: We measured urinary ETU, hair Mn, and blood Mn concentrations in samples collected 1–3 times during pregnancy from mothers enrolled in the Infants’ Environmental Health (ISA) study. We then assessed neurodevelopment in their 1-y-old infants using the Bayley Scales of Infant and Toddler Development, 3rd edition (BSID-III). We estimated exposure–outcome associations using linear regression models adjusted for maternal education, parity, gestational age at birth, child age, Home Observation for Measurement of the Environment score, and location of neurodevelopmental assessment. RESULTS: Median (P25–P75) urinary ETU, hair Mn, and blood Mn measured during pregnancy were [Formula: see text] (2.4–4.9; specific gravity–corrected), [Formula: see text] (0.9–4.1), and [Formula: see text] (20.3–28.0), respectively. Among girls, higher ETU was associated with lower social-emotional scores [[Formula: see text] (95% CI: [Formula: see text] , 0.4)], whereas higher hair Mn was associated with lower cognitive scores [[Formula: see text] ([Formula: see text] , 0.1)]. Among boys, higher hair Mn was associated with lower social-emotional scores [[Formula: see text] ([Formula: see text] , [Formula: see text])]. We observed null associations for blood Mn, language, and motor outcomes. CONCLUSIONS: Our findings indicate that maternal exposure to mancozeb and excess Mn during pregnancy may have adverse and sex-specific effects on infant neurodevelopment. https://doi.org/10.1289/EHP1955